Experience in the application of mixed reality for surgical planning of a giant meningioma: review and case report - RANC, Revista Argentina de Neurocirugia; Ochoa Guzmán, Sebastián Alberto; Mantilla, Penélope; Valerio, José (Revista Argentina de Neurocirugía, 2024)
Background: spatial computing technologies are increasingly applied in the healthcare system. They are used as tools for medical education, patient information, surgery planning, and as assistants during surgical procedures. Mixed reality allows interaction between the virtual and real world and its applications are rapidly increasing.Objective: communicate the usefulness of mixed reality in the surgical planning of brain tumors.Case description: a 67-year-old male patient with an aggressive meningioma treated with several previous surgeries was admitted due to a one-month history of cognitive disorders, behavioral disturbance, and progressive worsening of focal neurological deficits. MRI showed a left parasagittal frontoparietal-temporal (FPT) tumor with necrotic regions and mass effect. The Brainlab® mixed reality viewer was used for preoperative planning.Surgery: a frameless stereotactic resection of the brain tumor was performed. The holographic length of the tumor edges was compared to the actual tumor edges as seen after removal.Conclusion: the application of mixed reality technology in neurosurgery shows good results. Although studies have found an improvement in the surgeon's experience in the presurgical area, the use of this technology in the intraoperative area is generating great expectations. It is still necessary to concretely demonstrate the benefits that the use of mixed reality provides to the patient, and this is still the most important task to study.
Keywords: Augmented reality; Brain tumor; Mixed reality; Neurosurgery